2014
DOI: 10.1121/1.4890640
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between multipulse integration and speech recognition with cochlear implants

Abstract: Comparisons of performance with cochlear implants and postmortem conditions in the cochlea in humans have shown mixed results. The limitations in those studies favor the use of within-subject designs and non-invasive measures to estimate cochlear conditions. One non-invasive correlate of cochlear health is multipulse integration, established in an animal model. The present study used this measure to relate neural health in human cochlear implant users to their speech recognition performance. The multipulse-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 55 publications
5
26
1
Order By: Relevance
“…These results echo our recent finding that the MPI slopes, which the current data suggest reflect temporal characteristics of the auditory nerve, predicted sentence, and phoneme recognition in noise (Zhou and Pfingst, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…These results echo our recent finding that the MPI slopes, which the current data suggest reflect temporal characteristics of the auditory nerve, predicted sentence, and phoneme recognition in noise (Zhou and Pfingst, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…To date, we have achieved SGN preservation at greater than 70% of normal in guinea pigs only when IHCs are present. However, in human subjects who have no measurable hearing and thus probably have poor IHC survival, we find that some stimulation sites do have steep MPI functions (Zhou et al, 2012; Zhou and Pfingst, 2014a). Also, from published reports we know that human subjects can maintain SGN densities at high levels for long periods of time in the absence of IHCs (e.g., Hinojosa and Marion, 1983).…”
Section: Relation Of Cochlear Health To Implant Function In Animalsmentioning
confidence: 73%
“…In 8 bilaterally implanted listeners with different degrees of ear asymmetry, we found that the ears with better cochlear health as estimated by the slopes of the MPI functions were also those that performed better in sentence recognition in an amplitude-modulated noise background and phoneme recognition at challenging signal to noise ratios (SNRs) (Zhou and Pfingst, 2014a). The magnitude of ear differences in the MPI slopes also proportionally predicted the magnitude of the subjects’ ear differences in speech reception thresholds (signal to noise ratios required for 50% correct recognition of CUNY sentences), consonant recognition at 0 dB SNR, and perception of the place of articulation feature of consonants.…”
Section: Relation Of Cochlear Health To Implant Function In Animalsmentioning
confidence: 99%
“…In humans with CIs who do not have measurable residual hearing, MPI slopes have been shown to vary with similar magnitudes as those found in animals with a range of haircell conditions, suggesting that hair cells are not essential for MPI and that SGN density is more likely the anatomic variable that is responsible for MPI slopes (Zhou et al, 2012;Zhou and Pfingst, 2014). An important difference between previously published studies in guinea pig and human subjects with CIs is that the position of the electrodes with respect to the modiolus was relatively constant in the guinea pig experiments but varied considerably in the human subjects.…”
Section: Introductionmentioning
confidence: 82%